PENINGKATAN PENGETAHUAN DAN PERILAKU SARAPAN PADA ANAK SEKOLAH DASAR DENGAN MEDIA VIDEO STOP MOTION - Winalda Dinda; Mulus Gumilar; Umi Mahmudah; Agung Suprihartono (Jurusan Gizi Poltekkes Kemenkes Bandung, 2022)
Breakfast is an important thing, but it is often neglected due to inadequate knowledge and bad attitude about the importance of breakfast. The data shows that 44.6% of elementary school-aged children consume a low-quality breakfast, which energy intake of less than 15% of their daily nutritional needs. Nutrition education should be given to increase knowledge and behavior of breakfast. The media used is stop motion video. The purpose of this study was to determine the effect of nutrition counseling with stop motion videos and power points on the knowledge and behavior of breakfast in the students of SDN Semplak Barat 2 Bogor. Research method is Quasy Experiment with control group pre-test and post-test design. The sample of this study was fifth grade students with the number of samples divided into two, the treatment group was given stop motion video (n = 20) and the control group was given power point (n = 20). The results showed that there was an effect of nutrition education on knowledge and behavior before and after being given stop motion video and Power Point with a value of p <0.05 (p = 0.000), then there was no significant difference in average between giving treatment using stop motion video with power point in nutrition counseling on knowledge (p value = 0.876) and breakfast behavior (p value = 0.611) with p value> 0.05. Counseling needs to involve parents.